2022
DOI: 10.1155/2022/7802334
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis, Prevention, and Treatment of Radiotherapy-Induced Xerostomia: A Review

Abstract: In patients with head and neck cancer, irradiation (IR)-sensitive salivary gland (SG) tissue is highly prone to damage during radiotherapy (RT). This leads to SG hypofunction and xerostomia. Xerostomia is defined as the subjective complaint of dry mouth, which can cause other symptoms and adversely affect the quality of life. In recent years, diagnostic techniques have constantly improved with the emergence of more reliable and valid questionnaires as well as more accurate equipment for saliva flow rate measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 164 publications
(245 reference statements)
0
12
0
Order By: Relevance
“…The patient's response to radiation therapy is individual and depends on the radiation dose and treatment area. Radiotherapy contributes to short-term dryness or total lack of salivary production [18] .…”
Section: Results and Discussion 31 Etiologymentioning
confidence: 99%
“…The patient's response to radiation therapy is individual and depends on the radiation dose and treatment area. Radiotherapy contributes to short-term dryness or total lack of salivary production [18] .…”
Section: Results and Discussion 31 Etiologymentioning
confidence: 99%
“…Some studies have found that drinking water frequently can be as effective as using saliva substitutes. Mucoadhesive discs of xylitol or sugar-free gum have been used with varying results [83][84][85][86][87][88].…”
Section: Managementmentioning
confidence: 99%
“…In recent years, clinically validated dose constraints have been established for salivary-associated OARs, such as parotid glands, submandibular glands, and oral cavities. With the introduction of IMRT, oncologists could use an inverse planning algorithm and multiple fields to spare OARs from toxic threshold doses [ 87 , 88 ].…”
Section: Reviewmentioning
confidence: 99%
“…Other clinical investigations demonstrated that radiation therapy in the head-neck area leads to the disruption of the mucin micro-network of saliva [17]. As a result, the water-retention and adhesive functions of saliva are weakened or lost, contributing to the development of xerostomia (i.e., dry mouth) and oral mucositis [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The state-of-the-art therapeutic interventions to reduce dry mouth or slow down the development of oral mucositis are topical treatments, such as saliva-replacement fluids or gels containing polysaccharides, such as carboxy-methylcellulose, glycerol, or polyethylenoxide; xanthan gum; or mucins [20][21][22]. However, several studies have shown that the effect of most marketed saliva substitutes is limited [14,19,23,24]. The disadvantages include a short duration of action, an unpleasant feeling in the mouth, or a limited effect on the prevention of enamel and dentin demineralization [14,19,25].…”
Section: Introductionmentioning
confidence: 99%